Analysis of Consumer Preferences in Buying Mix Cereal - Theresia, Theresia; Rohmandiyas, Nanang Agung (Budapest International Research and Critics University, 2021)
The biggest contribution to the cereal market share is the mix cereal category (78%) which currently has few players. There is a huge potential for FMCG companies to enter the mix cereal business, which is still growing. In this competitive era, of course, we need the right marketing strategy to be able to meet market needs and demands. Therefore, this study aims to analyze consumer preferences in choosing mix cereals with the convenience sampling method which was distributed in the form of an online questionnaire to 100 women aged 25-45 years. Then the results were analyzed using the conjoint analysis method. In this study, it was found that the producer's attributes became the most important factor in consumers' consideration of choosing mix cereals, followed by taste, price, and nutrition. Higher consumer preferences are found in the combination of mixed cereal products with chocolate flavor and there are fiber claims on the packaging which are sold with a price range of Rp. 1,200, - up to Rp. 1.850,- produced by Wingsfood. This can be a reference for FMCG companies to apply and develop a mix cereal product that can be launched to enter the cereal business in Indonesia.